The Role of the Jordanian Educational System in Reducing the Negative Impact of the Means of Modern Communication Technology on the Education of Youth People from the Perspective of their Teachers - Al-Zboun , Mohammad; Atiah, Nariman (Jordan Journal of Educational Sciences, 2016)
This study aimed to identify the role of the Jordanian educational system to reduce the negative impact of the modern communication technology on the education of youth people. The study sample consisted of 128 teachers were chosen randomly, for the semester 2013/2014, and it used the survey method. The study was develop a questionnaire included two directions: the identification of the role and consisted of (20) items. Identifying problems and consisted of (32) paragraphs and the number of dimensions is (4) dimensions. The study found the following results: The overall appreciation of the role of the educational system to reduce the negative impact on the education of young people came moderately. The overall appreciation of the existence of problems arising from the use of modern communication technology to raising youth came high. In addition, ranked dimensions of the degree of the problem: the following order of ethical and religious dimension, then the social and economic dimension, then the health and sexual dimension, then the psychological and emotional dimension